The United Nations Alliance of Civilizations and Interfaith Dialogue: What is it Good For? - Haynes, Jeffrey (The review of faith & international affairs, 2018)
The United Nations Alliance of Civilizations (UNAOC) was founded in 2005, following the devastating attacks by al Qaeda on the United States on 11 September 2001 ('9/11'). The article examines the UNAOC's involvement in interfaith dialogue by focusing on three faith-based entities with which the Alliance regularly cooperates in joint interfaith events: The Committee of Religious NGOs at the United Nations, Religions for Peace, and United Religions Initiative. The article concludes by suggesting that, while such cooperation is no doubt well-meaning and probably does no harm, it is unclear whether it actually advances the goals of interfaith dialogue and cooperation: reduced tensions and conflicts.